Mechanics of slackened systems - Gawęcki, Andrzej (Computer Assisted Methods in Engineering and Science, 1994)
The paper concerns slackened systems, i.e . discrete deformable systems with gaps (clearances) at structural joints. The mathematical model of stich systems coincides with a FEM-oriented approximation of loelcing-e1astic-plastic bodies. The theory describes a relatively wide clus of systems made of time-independent materials. The problem of slackened systems has been developed during the last decade. The work presents the current state of knowledge in this field.